Least-mean-square routing with load-balancing for wireless ad hoc networks - 陈西豪 陈惠民 周伟 (Journal of Shanghai University, 2008)
Routing algorithm is a challenge for a mobile ad hoc network （MANET）, but current routing protocols for MANETs consider the path with minimum number of hops as the optimal path to a given destination. This strategy does not balance the traffic load over a MANET, and may result in some disadvantages such as creating congested area, depleting power faster and enlarging time delay in the nodes with heavy duties. In this paper, we propose a routing scheme that balances the load over the network by selecting a path based on its mean load-square, the proposed routing metric can reflect not only the load of the path, but also the load distribution along the path. Simulation results show effectiveness of this routing scheme on balancing the load over all nodes in the network.